2015
DOI: 10.1038/srep17517
|View full text |Cite
|
Sign up to set email alerts
|

Large genomic fragment deletion and functional gene cassette knock-in via Cas9 protein mediated genome editing in one-cell rodent embryos

Abstract: The CRISPR-Cas RNA-guided system has versatile uses in many organisms and allows modification of multiple target sites simultaneously. Generating novel genetically modified mouse and rat models is one valuable application of this system. Through the injection of Cas9 protein instead of mRNA into embryos, we observed fewer off-target effects of Cas9 and increased point mutation knock-in efficiency. Large genomic DNA fragment (up to 95 kb) deletion mice were generated for in vivo study of lncRNAs and gene cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 43 publications
0
55
0
1
Order By: Relevance
“…Wang et al [30] reported a 95 kb deletion in mice. Recently, we demonstrated generation of mice carrying deletions of 0.5, 2, and 5 Mb and an inversion of 5 Mb [31,32].…”
Section: Reproduction Of Diseases In Mice Carrying Chromosome Rearranmentioning
confidence: 99%
“…Wang et al [30] reported a 95 kb deletion in mice. Recently, we demonstrated generation of mice carrying deletions of 0.5, 2, and 5 Mb and an inversion of 5 Mb [31,32].…”
Section: Reproduction Of Diseases In Mice Carrying Chromosome Rearranmentioning
confidence: 99%
“…Therefore, this system can be used to generate genetically modified mice rapidly by microinjecting sgRNAs with Cas9 into fertilized eggs [4,5,6,7,8,9]. Several studies have reported the induction of an efficient CRISPR/Cas9-mediated genomic rearrangement such as deletion or inversion of ~100 kb [10,11,12]. However, the maximum size of indels that can be induced by the CRISPR/Cas9 system is still unclear.…”
mentioning
confidence: 99%
“…Although the ribonuceoprotein complexes of recombinant Cas9 protein combined with synthetic guide RNAs have been demonstrated as effective genome editing tool [12][13][14], their efficiency is still much lower than the conventional plasmid transfer approach. Thus, the plasmid based approach would be the mostly used method in the coming years and scientists working on improving the efficiency of custom guide RNA cloning and IVT (in vitro transcription) synthesis will appreciate the strategy employed here.…”
Section: Discussionmentioning
confidence: 99%